2011
DOI: 10.5586/asbp.2011.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of Fraxinus angustifolia Vahl in the north-western Balkans

Abstract: Fraxinus angustifolia Vahl is a species native in the north-western Balkans, where it has a divided range. Most of its range is located in flood-prone riparian sites in the Pannonian plain but the species is also found on humid sites along some rivers in the Submediterranean region. We analysed morphologic variation within and between five populations (14 trees/population) located in the Subpannonian and Submediterranean region of Slovenia. Thirty two characters were assessed on ca. 80 leaves from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…By partitioning the total variance to sources of variability for four of the eight studied morphological characteristics, [25] found a greater inter-population variability in comparison with the intra-population one. Contrary to that, in the studies of leaf variability of widely distributed woody species by methods of classic morphometric analysis, it is common for a greater share in the overall variability to be accounted for by the variability of trees within populations [25,31,33,51]. Although the service tree populations in Croatia demonstrated a high degree of interpopulation variability, the study also found a high variability between trees within populations, which suggested a high gene flow between populations.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…By partitioning the total variance to sources of variability for four of the eight studied morphological characteristics, [25] found a greater inter-population variability in comparison with the intra-population one. Contrary to that, in the studies of leaf variability of widely distributed woody species by methods of classic morphometric analysis, it is common for a greater share in the overall variability to be accounted for by the variability of trees within populations [25,31,33,51]. Although the service tree populations in Croatia demonstrated a high degree of interpopulation variability, the study also found a high variability between trees within populations, which suggested a high gene flow between populations.…”
Section: Discussioncontrasting
confidence: 37%
“…In addition to genetic markers, morphological traits were also used. Although in comparison with molecular markers their significance has recently been on the decrease, morphological traits are still frequently applied [25,[31][32][33]. This is supported by an increasing amount of research combining methods of morphometric and molecular analysis [34][35][36].…”
Section: Introductionmentioning
confidence: 94%
“…A total of 45 traits were measured on the leaves as shown in Figure 2 and Table 2 following Gonzalez-Rodrigues and Oyama (2005), Brus et al (2011), Jarni et al (2011), and Poljak et al (2015) methods. Leaflet measurements were conducted using a digital caliper with 0.01 mm accuracy of measurements.…”
Section: Measurement Of Morphological Traitsmentioning
confidence: 99%
“…The high variation within populations might be in part the expression of phenotypic plasticity and/or instability development due to micro-environmental conditions experienced by each tree, but it might be also the result of genotypes differences among individuals. In the studies of leaf morphometric analysis of widely distributed species, the greater variability is common existed within populations (Brus et al 2011;Jarni et al 2011;Poljak et al 2015). High variability within population of E. apiculata might be caused by high gene flow between individuals.…”
mentioning
confidence: 99%
“…F. angustifolia is a hermaphrodite with variable morphology that enabled the establishment of several taxa based on differences in the samara and leaf morphology (Papi et al, 2011). In addition, hybridization between F. angustifolia and F. excelsior is possible, which has been reported by various groups (Papi et al, 2011) based on the observation of intermediate morphologies (Fernández-Manjarrés et al, 2006;Jarni et al, 2011), the genotyping of natural populations (Jeandroz et al, 1996;Papi et al, 2011;Temunović et al, 2012) and the assessment of the morphological and genetic structure of putative hybrid populations (Fernández-Manjarrés et al, 2006;Gerard et al, 2013). Due to hybridization and description of many subspecies based on high variation in morphology, the taxonomic status of F. angustifolia is most complicated (Wallander, 2008).…”
Section: Introductionmentioning
confidence: 63%